ANALISIS PENGARUH MANAJEMEN HUBUNGAN PELANGGAN TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING (Pada Pelanggan Jasa Ekspedisi Pengiriman Barang TIKI di Kecamatan Banjarsari, Kota Solo) - Setyowiseso, Bagas; Sutopo, Sutopo (Faculty of Economics and Business Diponegoro University, 2018)
Company in retaining customers need to increase loyalty by means of customer relationship management (CRM) strategy. To analyze the strategy the aim of this study to know the relationship of continuity marketing (X1), one to one marketing (X2), partnering program (X3), to customer loyalty (Y2), with customer satisfaction intervention (Y1). Sampling method using purposive sampling with technique of non-probability sampling at PT. Citra Van Titipan Kilat (TIKI), with the number of samples taken 182 customers who have used TIKI services.Based on the results of this research that continuity marketing (X1) and one to one marketing (X2) have a positive and significant effect on the customer loyalty (Y2), with customer satisfaction intervention (Y1). Meanwhile, partnering program (X3) has no effect on the customer loyalty (Y2), with customer satisfaction intervention (Y1).